Antioxidant and cytotoxicity screenings of ethyl acetate extract from Annona muricata leaves and its fractions - Binawati Ginting; Mustanir Yahya; Nurdin Saidi; Ilham Maulana; Murniana Murniana; Eka Safitri; Muhammad Bahi; Yetty Rosiyana; Hazrina Novani; Devia Nurul Azla Milza (Wolters Kluwer Medknow Publications, 2024)
Leaves of Annona muricata have medicinal potential which has gained attention from researchers around the world. This study has an objective to screen the antioxidant and cytotoxicity of ethyl acetate extract from A. muricata leaves and its fraction. The fine powder of A. muricata was macerated in methanol and further partitioned using two different solvents, namely n-hexane and ethyl acetate. In this article, we reported the screening results for ethyl acetate extract. Fractionation was then performed on the extract by means of column chromatography by gradient elution resulting in five combined fractions. Brine shrimp lethality test and 1-diphenyl-2-pycrilhidrazil (DPPH) assays were employed to evaluate the cytotoxicity and antioxidant of the extract, respectively. Characterization using gas chromatography-mass spectroscopy (GC-MS) was then conducted. The cytotoxicity of the samples was indicated by median lethal concentration50 values ranging from 28.84 to 1023.3 ppm. As for the antioxidant activity, the DPPH median inhibitory concentration50 values ranged from 4.12 to 180.66 ppm. GC-MS analysis on the most bioactive fraction revealed the predominating phytochemical contents of neophytadiene, palmitic acid, and phytol. In conclusion, the fraction of ethyl acetate extract from A. muricata leaves could potentially act as a strong antioxidant and moderate cytotoxic agent.